"All They Do Is See the Charge": Reentry Barriers and Correctional Programming Needs of Women Returning to Society after Incarceration. Issue 4 (2nd October 2019) - Carter, Lisa M.
ABSTRACT: This study utilized a qualitative approach to examine formerly incarcerated women's perceptions of their reentry process and to understand the role correctional programming may have to alleviate the difficulties for this population when transitioning back into society. In-depth interviews were conducted with halfway house residents ( N  = 26). It is necessary for correctional personnel and policy makers to understand the needs of these women so that gender-responsive programming may be implemented in prisons to better prepare women to deal with the challenges of reentry.